Health education, nurses and creativity: the necessary interconnection to the educative process - Francisca Georgina Macêdo de Sousa; Marlene Gomes Terra; Kenya Schmidt Reibnitz; Vania Marli Schubert Backes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The object of this paper is to reflect upon the dimension of health education as a process of construction in comparison with the current pattern of health attention. It also intends to obtain a critical view upon nursing care and in the education of nurses, trying to look for strategies for an innovational and creative practice of health education. In this article, it is aimed to discuss realities and evidences as well as reassure necessities, transform situations and widen the awareness about the professional practice of nurses. Understanding health in its wide dimension demands from the professionals an articulation that is able to apprehend the way of thinking and the way of doing the routine of patients and professionals in the entireness of the human being. It aims, over all, the participation of professionals and the nursing team in the educative process in which they are introduced, acting as co-responsible in the caring of people's health.